2017
DOI: 10.1103/physrevb.96.045101
|View full text |Cite
|
Sign up to set email alerts
|

Semimetallic bands derived from interlayer electrons in the quasi-two-dimensional electride Y2C

Abstract: Two-dimensional (2D) electrides are a new concept material in which anionic electrons are confined in the interlayer space between positively charged layers. We have performed angle-resolved photoemission spectroscopy measurements on Y2C, which is a possible 2D electride, in order to verify the formation of 2D electride states in Y2C. We clearly observe the existence of semimetallic "electride bands" near the Fermi level, as predicted by ab initio calculations, conclusively demonstrating that Y2C is a quasi-2D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
(44 reference statements)
7
17
0
Order By: Relevance
“…Since the first demonstration of Ca 2 N as a Q2D electride, [3] studies on the magnetic, [5,7,8,9,10,11] optical, [12] and mechanical [13] properties of layered electrides have been reported. Angle-resolved photoemission spectroscopy (ARPES) measurements have successfully identified the Q2D anionic bands of Ca 2 N [14] and Y 2 C, [15] which are in excellent agreement with those predicted by ab initio calculations based on density functional theory (DFT). The surface electronic structures of layered electrides have been calculated recently: it was revealed that they possess an extra-surface state, i.e., a two-dimensional (2D) free-electron-like state with the electrons literally floating outside the surface.…”
Section: Introductionsupporting
confidence: 60%
“…Since the first demonstration of Ca 2 N as a Q2D electride, [3] studies on the magnetic, [5,7,8,9,10,11] optical, [12] and mechanical [13] properties of layered electrides have been reported. Angle-resolved photoemission spectroscopy (ARPES) measurements have successfully identified the Q2D anionic bands of Ca 2 N [14] and Y 2 C, [15] which are in excellent agreement with those predicted by ab initio calculations based on density functional theory (DFT). The surface electronic structures of layered electrides have been calculated recently: it was revealed that they possess an extra-surface state, i.e., a two-dimensional (2D) free-electron-like state with the electrons literally floating outside the surface.…”
Section: Introductionsupporting
confidence: 60%
“…We have also tried the patterning procedure by using Ag or Cu instead of Au, which leads to a similar effect but with weaker SOC. The discovery of more and more new electride materials holding anionic electrons [50,51], especially the experimentally synthesized layered electrides such as Y 2 C [45,52], provides a unique material platform to achieve the novel patterning procedure. The emergent 2D molecular crystals and metal-organic frameworks can serve as another category of candidates to materialize the proposed CT lattice model.…”
Section: E E H K T E E T E E T E E T E Ementioning
confidence: 99%
“…The DFT calculation has shown that ferromagnetic instability (Stoner type) in Y 2 C is indeed suppressed when considering the onsite Coulomb energy (U) for the 4d orbital [18]. Therefore, the absence of magnetic order as well as the appearance of localized moments at the Y site in the pc sample strongly suggest the importance of electron correlation in gaining a detailed understanding of the electronic ground state in Y 2 C. In fact, ARPES experiments have shown that the observed band structure is better described by DFT calculation where U for the 4d orbital [19] is taken into account. How- ever, we note that our result does not necessarily disfavor the recently suggested scenario that attributes the discrepancy between ARPES and DFT to the surface state stemming from "topological" nature of the electride band [28].…”
mentioning
confidence: 99%
“…1(a)] belongs to the space group R 3m with the lattice constant for the a (c)-axis being 3.6164 (17.9651) Å for Y 2 C. A DFT calculation suggests 2D elec-tride features similar to Ca 2 N [17] for this compound, where the electron band near the Fermi energy consists of Y 4d orbitals and the 2D electronic states are present between the Y layers. While these predicted band structures [14,17,18] have been confirmed by angle-resolved photoemission spectroscopy (ARPES) [15,19], the interesting possibility of ferromagnetic instability associated with electride bands, which has been suggested for Y 2 C [18] is yet to be observed experimentally.…”
mentioning
confidence: 99%